Izin Usaha Pertambangan diatas Tanah Masyarakat Adat Paser dalam Sudut Pandang Penalaran Hukum - Aditia Tri Putra; Annastasia Ockta Anggraini; Devina Michaela Laksmono; Wilda Ayu Anggraini (Universitas Batanghari Jambi, 2023)
Indonesia as a country has various styles of natural and cultural resources, one of which is the customary law community whose existence existed even before Indonesia's independence. The existence of customary law communities to obtain legal recognition is based on article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia and article 6 paragraph (2) of Law Number 39 of 1999 concerning Human Rights. Moreover, regarding customary land, it has been embodied in Article 3 of the UUPA which legally recognizes the existence of customary law which is the breath of this basic law. Nonetheless, customary land as land controlled by indigenous peoples is still a legal problem that often occurs, especially in the case of communal land disputes with mining business permits, one of which is the case of the Paser indigenous people. There is still a discrepancy between da sein and da solen where through the perspective of legal reasoning, law is not only limited to literal meanings and logical propositions by ignoring the context and purpose of law, but law should be present to protect society.